Microbial Communities and Functions in the Rhizosphere of Disease-Resistant and Susceptible Camellia spp. - Li, Jun; Zhang, Chenhui; Qu, Xinjing; Luo, Ziqiong; Lu, Sheng; Kuzyakov, Yakov; Alharbi, Hattan A.; Yuan, Jun; Niu, Genhua (Frontiers in Microbiology, 2021)
Oil tea (Camellia spp.) is endemic to the hilly regions in the subtropics. Camellia yuhsienensis is resistant to diseases such as anthracnose and root rot, while Camellia oleifera is a high yield species but susceptible to these diseases. We hypothesize that differences in the rhizosphere microbial communities and functions will elucidate the resistance mechanisms of these species. We used high-throughput sequencing over four seasons to characterize the rhizosphere microbiome of C. oleifera (Rhizo-Sus) and C. yuhsienensis (Rhizo-Res), and of the bulk soil control (BulkS). In Rhizo-Res, bacterial richness and diversity (Shannon index) in autumn and winter were both higher than that in Rhizo-Sus in the same season. In Rhizo-Res, fungal richness in autumn and winter, as well as diversity in summer, autumn and winter were higher than that in Rhizo-Sus in the same season. The seasonal variations of bacterial community structure were different, while that of fungal community structure was similar between Rhizo-Res and Rhizo-Sus. Gram-positive, facultatively anaerobic, and stress tolerant bacteria were the dominant groups in Rhizo-Sus, while Gram-negative bacteria were the dominant group in Rhizo-Res. The significant differences in bacterial and fungal functions between Rhizo-Sus and Rhizo-Res were : 1) In Rhizo-Sus, there were three bacterial and four fungal groups with plant growth promoting potentials, such as Brevibacterium epidermidis and Oidiodendron maius, and one bacterium and three fungi with pathogenic potentials, such as Gryllotalpicola sp. and Cyphellophora sessilis; 2) In Rhizo-Res, there were also three bacteria and four fungal groups with plant growth promoting potentials (e.g. Acinetobacter lwoffii and Cenococcum geophilum), but only one phytopathogen (Schizophyllum commune). In summary, the rhizosphere microbiome of disease-resistant C. yuhsienensis is characterized by a higher richness and diversity of microbial communities, more symbiotic fungal communities, as well as fewer pathogens compared to the rhizosphere of high-yield but disease-susceptible C. oleifera.